GNSS SATELLITE TECHNOLOGIES IN MONITORING SYSTEMS FOR DEFORMATIONS OF HYDRAULIC STRUCTURES (Journal of Geography and Environmental Management, 2026)
The article examines approaches to improving the accuracy of geodetic monitoring of deformations of hydraulic engineering structures through the integrated use of satellite GNSS technologies and traditional linear-angular measurements. The relevance of the study is determined by the need to ensure the safe operation of unique hydraulic structures of responsibility classes I and II under conditions of complex terrain, limited radio horizon, and significant seasonal temperature variations. The Ust-Kamenogorsk Hydropower Plant, located in the complex orographic conditions of the foothill zone of the Western Altai, was selected as the research object.During the study, a horizontal geodetic control network was established, including points of the state geodetic network, alignment reference points, and additional observation points located considering optimal conditions for satellite signal reception. Field measurements were carried out using dual-frequency geodetic GNSS receivers in the static mode of synchronous observations, followed by differential data processing and network adjustment using the least squares method. To refine the results, linear-angular measurements and analysis of the network geometry were additionally applied.The results showed that the root mean square errors of baseline length determination ranged from 0.8 to 1.1 mm, while after optimization of angular observations the accuracy of coordinate determination increased to 0.6–0.7 mm. It was experimentally confirmed that 30-minute GNSS observation sessions under favorable conditions provide accuracy comparable to 5-hour measurements. The study also demonstrated that the combined use of GNSS receivers and high-precision electronic total stations makes it possible to compensate for the limitations of satellite measurements and improve the reliability of deformation monitoring. The developed methodology can be recommended for the design of monitoring systems for unique hydraulic engineering structures and for ensuring their operational safety.
Keywords: hydraulic structures; geodetic monitoring; GNSS; trilateration; deformations; automated control systems; Ust-Kamenogorsk HPP